Sensory profiles in older adults with orthopedic conditions during quiet stance: a cross-sectional study - Marine Brika; France Mourey; Alexandre Kubicki (European Review of Aging and Physical Activity)
Abstract Background Pathological aging can impair sensory information, leading to postural control disorders in older adults. Compensatory sensorial mechanisms are emerging to preserve balance function. The objective of the study was to identify sensory profiles in functionally impaired older adults, and determine if they are linked to the frequently observed cervical proprioceptive disorders in this population. Methods Fifty-one older adults (76.9 ± 7.6 years) were divided into 2 Functional Groups (FG-/FG+) according to a composite score that included 3 variables (gait speed, grip strength and fear of falling). All the participants completed the modified clinical test of sensory interaction on balance (m-CTSIB) and the cervical joint sense position error (CJPSE) test. Exploratory factor analysis was used to identify common factors among the variables. Pearson correlation was used to examine relationships between variables. Results As expected, conditions 2 and 3 of the m-CTSIB were both challenging to balance, whereas condition 4 was too difficult for several patients. Factor analysis revealed that the stabilometric variables were grouped together in factor one, and proprioceptive performance (CJPSE) and the mean CoP velocity in m-CTSIB condition 3 formed another second factor. Moreover, a significant correlation was highlighted between stability in Condition 3 and CJPSE in the FG-. Conclusion Our results revealed the predominance of both visual and podal information in functionally impaired adults to control their posture. We speculate that the observed podal preference could be consecutive to a less efficient cervical proprioceptive system.